A pilot exploratory investigation on pregnant women's views regarding STan fetal monitoring technology - Kate Bryson; Chris Wilkinson; Sabrina Kuah; Geoff Matthews; Deborah Turnbull (BMC, 2017)
Abstract Background Women's views are critical for informing the planning and delivery of maternity care services. ST segment analysis (STan) is a promising method to more accurately detect when unborn babies are at risk of brain damage or death during labour that is being trialled for the first time in Australia. This is the first study to examine women's views about STan monitoring in this context. Methods Semi-structured interviews were conducted with pregnant women recruited across a range of clinical locations at the study hospital. The interviews included hypothetical scenarios to assess women's prospective views about STan monitoring (as an adjunct to cardiotocography, (CTG)) compared to the existing fetal monitoring method of CTG alone. This article describes findings from an inductive and descriptive thematic analysis. Results Most women preferred the existing fetal monitoring method compared to STan monitoring; women's decision-making was multifaceted. Analysis yielded four themes relating to women's views towards fetal monitoring in labour: a) risk and labour b) mobility in labour c) autonomy and choice in labour d) trust in maternity care providers. Conclusions Findings suggest that women's views towards CTG and STan monitoring are multifaceted, and appear to be influenced by individual labour preferences and the information being received and understood. This underlies the importance of clear communication between maternity care providers and women about technology use in intrapartum care. This research is now being used to inform the implementation of the first properly powered Australian randomised trial comparing STan and CTG monitoring.